Prevalence of trichostrongylids in small ruminants of Kashmir valley - ALLAIE, I M; SHAHARDAR, R A; TRAMBOO, S R; PRASAD, A; MOHMAD, AQUIL; WANI, Z A; BULBUL, K H (The Indian Journal of Animal Sciences, 2021)
The present study was undertaken to work out the population structure of trichostrongylids affecting the small ruminants of Kashmir valley. The faecal samples were collected from each zone and sector of the valley and were examined by qualitative as well as quantitative techniques for presence of trichostrongyle eggs, followed by coproculture using petridish method for harvesting of infective larvae. The overall prevalence revealed Haemonchus spp. to be the most predominant trichostrongyle worm followed by Trichostrongylus spp., Oesophagostomum spp., Teladorsagia spp., Chabertia spp. and other larvae, the difference being statistically significant. In south Kashmir, a different trend was observed for trichostrongyle worms with predominance of Trichostrongylus spp., followed by Haemonchus spp., Oesophagostomum spp. and other larvae, the difference being statistically significant (P